Los derechos de los niños, niñas y adolescentes a través de las medidas de protección emitidas por las juntas cantonales de protección de derechos. - Yépez, Ana D. (2020)
The present research work has the general objective of analyzing the rights of children and adolescents through the protection measures dictated by the Cantonal Boards for the Protection of Rights; and as specific objectives determine the rights that protect children and adolescents as a vulnerable sector of society, describe the protection measures issued by the Cantonal Protection Boards Rights in favor of children and adolescents and analyze the measures of protection issued by the Cantonal Boards of Protection of Law in favor of children and adolescents; considering that the problem is how to guarantee the rights of children and adolescents, through the guarantee measures dictated by the Cantonal Boards of Protection of Rights; It is important to indicate that the qualitative research methodology was used because it is social research; and, a type of descriptive investigation, to arrive at the conclusion of declaring that the Cantonal Board for the Protection of Rights in accordance with what is stated in both the Constitution of the Republic of Ecuador and the International Treaties; as well as in the Childhood and Adolescence Code, it is one of the organisms whose main objective is the Protection, Defense and Enforceability of the Rights of children and adolescents, and that being an administrative entity also forms part of the municipal administration, organized and financed by it.